THREE NEW NEPENTHES FROM SULAWESI TENGAH - TURNBULL, J. R.; MlDDLETON, A. T. (Research Center for Biology, 1984)
Three new high mountain forest taxa of Nepenthaceae are described from Central Sulawesi. The new species are Nepenthes glabratus, N. hamatus and N. infundibuliformis. Existing material at Herbarium Bogoriense indicated that all three are widespread in Central Sulawesi